Effects of Exposures to Cement Dust and Powder on Workers in Cement Distribution/Retail Outlets in Benin City, Nigeria (Biological Sciences - PJSIR, 2005)
This study investigated the effects of exposures to cement dust and powder on workers in fifteen cement distribution/retail outlets in Benin City, Edo State, South-West Nigeria. Forty workers from these retail outlets were initially surveyed by using detailed and open-ended questionnaires as well as oral interviews. Twenty of them were finally subjected to microbiological tests and medical examinations after series of oral interviews and depending on the physical effects of the cement dusts on their skins. Skin, nose and eye swabs, as well as sputum samples of the subjects were collected and cultured using various growth media. Organisms isolated included Staphylococcus aureus, Branhamella catarrhalis, Bacillus spp., Klebsiella pneumoniae, Streptococcus and Proteus species, and some fungi, including Penicil- lium, Aspergillus, Trichophyton, Mucor and Epidermophyton species. Chest radiographs were also done to detect the occurrence of silicosis (occupational asthma). The results of this study have shown that depending on the length and level of exposure to cement dust and powder, effects may range from contact dermatitis, skin rash, immediate or delayed irritation of the eyes, as well as chest infections.